Hypoxanthine guanine phosphoribosyl transferases SmHGPRTases functional roles in Schistosoma mansoni - Batista, Izabella Cristina Andrade; Gava, Sandra Grossi; Tavares, Naiara Clemente; Calzavara-Silva, Carlos Eduardo; Mourão, Marina Moraes (Frontiers in Microbiology, 2022)
Extracellular/environmental stimuli trigger cellular responses to allow Schistosoma sp. parasites adaptation and decide development and survival fate. In this context, signal transduction involving eukaryotic protein kinases (ePKs) has an essential role in regulatory mechanisms. Functional studies had shown the importance of MAPK pathway for Schistosoma mansoni development. In addition, early studies demonstrated that Smp38 MAPK regulates the expression of a large set of genes, among them the hypoxanthine-guanine phosphoribosyl transferase 1 (SmHGPRTase 1, Smp_103560), a key enzyme in the purine salvage pathway that is part of a family comprising five different proteins. First, the regulation of this gene family by the MAPKs pathways was experimentally verified using Smp38-predicted specific inhibitors. In silico analysis showed significant differences in the predicted structure and the domain sequence among the schistosomal HGPRTase family and their orthologs in humans. In order to interrogate the HGPRTases (Smp_103560, Smp_148820, Smp_168500, Smp_312580 and Smp_332640, henceforth SmHGPRTase –1, -2, -3, -4, -5) functional roles, schistosomula, sporocysts, and adult worms were knocked-down using specific dsRNAs. Our results suggest that SmHGPRTases activity has an essential role in sporocysts and schistosomula development since significant differences in viability, size, and/or shape were observed after the in vitro knockdown. Also, the- knockdown of SmHGPRTases in schistosomula influenced the ovary development and egg maturation in female adult worms during mammalian infection. We also observed alterations in the movement of female adult worms knocked-down in vitro. Most of these results were shown when all gene family members were knocked-down simultaneously, suggesting a redundant function among them. Thus, this study helps to elucidate the functional roles of the SmHGPRTase gene family in the S. mansoni life cycle and provides knowledge for future studies required for schistosomiasis treatment and control.